2006
DOI: 10.1111/j.1601-183x.2006.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the glutamate receptor subunit gene GRIN2B with attention‐deficit/hyperactivity disorder

Abstract: The glutamatergic signaling pathway represents an ideal candidate susceptibility system for attention-deficit/ hyperactivity disorder (ADHD). Disruption of specific Nmethyl-D-aspartate-type glutamate receptor subunit genes (GRIN1, 2A-D) in mice leads to significant alterations in cognitive and/or locomotor behavior including impairments in latent learning, spatial memory tasks and hyperactivity. Here, we tested for association of GRIN2B variants with ADHD, by genotyping nine single nucleotide polymorphisms (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 75 publications
(88 reference statements)
2
80
0
Order By: Relevance
“…Both GRM5 and GRM7 (above) belong to the glutamatergic receptor gene family hypothesized to play a role in ADHD. [43][44][45] The GRM5 variant, a hemizygous deletion of 82 kb (11 SNPs; Supplementary Figure S2), showed uniparental inheritance and was experimentally validated by FISH (Figure 1). Neuropsychiatric assessment indicated that all three children in this family, one 18-year-old male and two females with ages 15 and 11, met the criteria for Table 2 are listed in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 98%
“…Both GRM5 and GRM7 (above) belong to the glutamatergic receptor gene family hypothesized to play a role in ADHD. [43][44][45] The GRM5 variant, a hemizygous deletion of 82 kb (11 SNPs; Supplementary Figure S2), showed uniparental inheritance and was experimentally validated by FISH (Figure 1). Neuropsychiatric assessment indicated that all three children in this family, one 18-year-old male and two females with ages 15 and 11, met the criteria for Table 2 are listed in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 98%
“…cerebral cortex ͉ glutamatergic signaling ͉ regulatory RNA N MDA receptors (NMDA-R) control many executive brain functions, such as working memory, and their dysfunction is implicated in a host of brain disorders (1)(2)(3)(4). Notably, hypofunctional NMDA-R signaling, particularly in the prefrontal cortex (PFC), has been implicated in the cognitive and behavioral disturbances characteristic of schizophrenia (5), autism (6,7), attention deficit hyperactivity disorder (ADHD) (8,9), mood disorders (10), and other psychiatric illnesses.…”
mentioning
confidence: 99%
“…Genetic variations of GRIN2B have been implicated in the genetic susceptibility to neuropsychiatric disorders other than OCD, including attention-deficit/hyperactivity disorder, 53 dyslexia, 54 schizophrenia and bipolar disorder (for a review, see Cherlyn and colleagues 34 ). Moreover, Parkinson disease and Huntington disease, 2 neurologic conditions in which obsessive-compulsive symptoms are not rare, have also been associated with changes in the function of the NR2B-containing NMDA receptors (for a review, see Loftis and Janowsky…”
mentioning
confidence: 99%